2016
DOI: 10.1371/journal.ppat.1005362
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Based Analyses of the JC Virus T-Antigen F258L Mutant Provides Evidence for DNA Dependent Conformational Changes in the C-Termini of Polyomavirus Origin Binding Domains

Abstract: The replication of human polyomavirus JCV, which causes Progressive Multifocal Leukoencephalopathy, is initiated by the virally encoded T-antigen (T-ag). The structure of the JC virus T-ag origin-binding domain (OBD) was recently solved by X-ray crystallography. This structure revealed that the OBD contains a C-terminal pocket, and that residues from the multifunctional A1 and B2 motifs situated on a neighboring OBD molecule dock into the pocket. Related studies established that a mutation in a pocket residue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The strong repressive function of the V392G substitution in TAg might be associated with the low expression of TAg, the ensuing production of other viral proteins, and the inhibition of viral replication. A recent study demonstrated that a single amino acid change in the C-terminal pocket of the TAg origin-binding domain impaired the role of TAg in DNA replication, suggesting that the conformational structure of TAg is crucial for its function (41). Because V392 in TAg is highly conserved among human polyomaviruses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The strong repressive function of the V392G substitution in TAg might be associated with the low expression of TAg, the ensuing production of other viral proteins, and the inhibition of viral replication. A recent study demonstrated that a single amino acid change in the C-terminal pocket of the TAg origin-binding domain impaired the role of TAg in DNA replication, suggesting that the conformational structure of TAg is crucial for its function (41). Because V392 in TAg is highly conserved among human polyomaviruses (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The major gene product encoded by the early region of the JCV genome is large T antigen (T-ag), a 688-residue modular protein that has an N-terminal J domain, an origin binding domain, and C-terminal helicase domain (reviewed in references [33][34][35][36][37]; the structures of the JCV T-ag origin binding domain (38,39) and helicase domains (40) have been recently solved. JCV T-ag accumulates in the nuclei of glial cells derived from PML patients (41).…”
Section: The G144 Oligodendrocyte Precursor Cell Line Supports Robustmentioning
confidence: 99%
“…The T-antigen origin-binding domain has a C-terminal pocket where both A1 and B2 motifs exist. Its F258 region is highly dynamic and responsible for DNA binding ( 4 ). Its N-terminal phosphorylation at threonine 125 is likely mediated by Cyclin-CDK, critical to binding retinoblastoma protein (Rb) p107 and p130, and maintaining Rb-E2F complexes ( 5 ).…”
Section: Introductionmentioning
confidence: 99%